Cytoadherence between endothelial cells and P. falciparum infected and noninfected normal and thalassemic red blood cells - Punnee Butthep (2018)
Background: Cytoadhesion of P. falciparum infected red blood cells (RBCs) to endothelial cells (ECs) is an important phenomenon that causes cerebral malaria in man. Reduced adhesion especially in thalassemia and hemoglobinopathies may be related to a protective mechanism against malaria in such people. Methods: The cytoadherence assay was performed using both conventional and floating conditions between ECs (ECV 304) and P. falciparum infected and noninfected RBCs from both normal and thalassemia subjects. In floating condition, RBC was fluorescently labeled with anti-glycophorin A antibody, whereas EC was identified by surface expression of PECAM-1, CD-36, ICAM-1, and E-selectin. The condition of floating EC was similar to the condition for subcultivation as they can adhere or bind to any surface. The phosphatidylserine (PS) exposure was also determined by using flow cytometer. Results: The adhesion of noninfected heterozygous thalassemic RBCs (all genotypes) to ECs was significantly increased as compared with normal RBCs (P < 0.02). Interestingly, after P. falciparum infection, the number of normal RBCs bound to ECs was significantly increased as compared with noninfected RBCs (P < 0.01), whereas heterozygous thalassemic RBCs infected by P. falciparum showed no significant difference compared with noninfected RBCs. In addition, we found a similar level of PS exposure in normal and thalassemic infected RBCs, which was related to the cytoadherence phenomenon. Conclusion: The reduced adhesion between heterozygous thalassemic RBCs infected by P. falciparum to ECs provides an explanation for their protective mechanism against malaria, as increased adhesion is a high risk for cerebral malaria and nonbinding infected RBCs can be removed by the reticuloendothelial system and other mechanism(s) in vivo. © 2006 International Society for Analytical Cytology.